Thermo-Electric Design of the Protection and Diagnostic Feeders of the HL-LHC Triplets. Issue 1 (March 2020) - Pasdeloup, F.; Prin, H.; Williams, L.
Abstract: The HL-LHC Project currently undertaken by CERN that provides an upgrade to the existing LHC accelerator, is designed to increase the luminosity of the colliding particle bunches by a factor of at least five. Part of this upgrade will require the replacement of the existing groups of three superconducting LHC triplet magnets situated on each side of the ATLAS and CMS detectors with similar groups of four higher field HL-LHC triplet magnets of a new design that exploit coils manufactured with cables in Nb3Sn superconducting alloy. The HL-LHC triplet magnets require dedicated electric current feeders linking their cold masses to their cryostat vacuum vessels, thermo-electrically optimised and specifically designed to separately feed their quench protection, beam tuning and instrumentation systems with electric current. The HL-LHC instrumentation feedthrough system is similar, though containing a larger cable inventory, to that mounted on existing cryo-magnets in the LHC accelerator whereas the quench protection and beam tuning systems, both present new requirements calling for a substantially different design approach. Installed in a highly activated zone of the LHC, all three systems consequently exploit only natural heat convection to prevent the formation of condensation at their warm ends. This paper describes the functional design and thermo-electrical optimisation achieved for each of these electric current feeder systems.